Correlation between low density lipoprotein subtype and acute cerebral infarction in patients with type 2 diabetes mellitus - ZHANG Renhe; YUAN Tailei; WANG Yurong; WANG Yan (Zhongguo linchuang yanjiu)
Objective To investigate the relationship between low density lipoprotein (LDL) subtypes and acute cerebral infarction (ACI) in type 2 diabetes mellitus (T2DM). Methods A retrospective analysis was conducted on 292 T2DM patients admitted to Nanjing Jiangbei Hospital from October 2020 to December 2022. According to the brain magnetic resonance examination results, the patients were divided into T2DM without ACI group (group A,n=157) and T2DM with ACI group (group B,n=135). High resolution polyacrylamide gel electrophoresis and automatic biochemical analyzer (Beckman AU5800) were used to measure the levels of each LDL subtype and total cholesterol (TC) of the two groups of subjects, and compare the differences of blood lipids among the groups under traditional risk factors. Logistic regression analysis was used to identify risk factors for T2DM combined with ACI. Results The LDL2, LDL3, LDL4, LDL5, TC, LDL in group B were significantly higher than those in group A (P＜0.05). Multivariate logistic regression analysis showed that elder age, hypertension, high levels of LDL2 and LDL4 were independent risk factors for T2DM complicated with ACI; The ROC curve showed an AUC of 0.843. Conclusion Compared with simple T2DM, the level of LDL2, LDL3, LDL4, and LDL5 are significantly increased in T2DM combined with ACI, and high levels of LDL2 and LDL4 may be independent risk factors for T2DM patients combined with ACI.